Analisis Kinerja Sistem Resi Gudang (SRG) Komoditas Pertanian di Provinsi Jawa Barat - Gunawan, Endro; Setiani, Rima (2017)
Warehouse Receipt System (WRS) is a government policy that aims to help farmers obtain the price of agricultural products at a favourable price through a delayed sale system. Agricultural commodities stored in WRS must meet certain quality and quantity requirements, so there is a quality guarantee for traders or distributors to get quality agricultural products. Through WRS Farmers get price assurance and marketing of agricultural products. The objectives of the research : To analyse performance of Warehouse Receipt System for agricultural products in West Java Province. The results of the study obtained information that the WRS implemented since 2008 implementation is slow. Stakeholders involved too much and the procedures are too long ranging from farmers, warehouse managers, assessment agencies (LPK) and financial institutions. The performance of WRS in Tasikmalaya District in 2015 has been utilized by 15 users with the number of maize successfully stored in WRS Jamanis warehouse reached 386.52 tons or equivalent of maize value of Rp 1, 623 billion. The number of WRS proposed as credit collateral amounts to 12 WRS with a total realization of Rp 900 million. The cost component charged for WRS maize user is the cost of quality test of Rp 280.000 per 1 WRS, transportation cost Rp. 10-20 / kg, drying cost Rp. 200 / kg and insurance costs Rp. 0.24 per item value. The minimum amount of maize to stored in warehouses is 25 tons.